Incorporation of a Physical Education and Nutrition Program Into Neurosurgery: A Proof of Concept Pilot Program. Issue 4 (October 2016) - Spiotta, Alejandro M.; Fargen, Kyle M.; Denham, Sarah L.; Fulton, Megan E.; Kellogg, Ryan; Young, Emily; Patel, Sunil; Turner, Raymond D.
Abstract : BACKGROUND: Balancing the demands of a busy medical career with personal wellness can be daunting, and there is little education on these principles available to physicians in training. OBJECTIVE: To implement a voluntary wellness initiative in our neurosurgery department to promote healthy lifestyle choices. This report details the baseline data collected as part of this quality improvement initiative. METHODS: The wellness initiative was implemented in July 2015 and available to all faculty and resident physicians in the Department of Neurological Surgery in collaboration with the Medical University of South Carolina Wellness Center. All participants were provided a Fitbit Surge HR wrist monitor (Fitbit, Boston, Massachusetts) and underwent baseline physical and psychological testing. RESULTS: Six faculty physicians and 9 residents participated. Overall physical fitness levels varied widely between subjects. Health screening demonstrated abnormalities in 80% of participants (elevated systolic blood pressure in 60%, elevated diastolic in 47%, elevated serum low-density lipoprotein in 53%). Body composition analysis demonstrated body weight higher than ideal in 69% (47% overweight; 13% obese). Recommended average body fat mass reduction was 25.4 pounds. Seventy-nine percent reported below-average quality of life compared with the average healthy adult. All subjects reported wanting more time for personal health. CONCLUSION: Baseline health and psychological screenings in our department demonstrated alarmingly prevalent, previously undiagnosed abnormalities on cardiovascular and body weight screenings. Obstacles to leading a healthier lifestyle have been identified and solutions have been incorporated into the program. This quality improvement initiative may serve as a template for other programs seeking to improve physician physical and mental well-being. ABBREVIATIONS: BMI, body mass index ESS, Epworth Sleepiness Scale HR, heart rate Abstract : Supplemental Digital Content is Available in the Text.